Hut 1 of Tornambé, Pietraperzia: an Experimental Project for Prehistoric Sicily Studies - Claudia Speciale; Kati Caruso (EXARC Journal, 2016)
Architectural reconstructions in archaeology represent very common experimental projects throughout Northern and Southern Europe (see for example Page 2012; Burrow 2015). Testing hypotheses and comparing scarce archaeological data with material culture artefacts helps to create an enduring visual experience for both researchers and the public (Paardekooper 2013).